B2B in Asian chemical industry - Kang, Minji (KDI School, 2001)
Maximized profit with minimal input; this is the foremost and eternal goal of business sector in capitalized society. Internet-savvy business people, in 21st century, have sought for the solution of continuous hunger for achieving efficiency in workflow and cost saving in the networked economy. Reducing marketing cost, saving telecommunication expenses, expanding new opportunities to new customers, accomplishing price transparency, and most importantly, controlling the whole process of business flow from production, sales to payment through networking individual companies' back-end system were believed to be finally achieved through a magic tool, internet business. Unlike people's expectation, however, the B2B concept itself is unfamiliar to most of the people and employing this new tool in such a conservative industry as chemical industry is being challenged in many facets. Many start-ups have been sprouted, but couldn't survive long. Most surviving B2Bs are also struggling and continuously being tested about their viability. New business models are continuously emerging without a strong confidence. We will see how this new industry would evolve, whether or not this would be developed as a powerful tool to be able to replace the inefficient offline trading practices after all.
Thesis(Master) --KDI School:Master of Public Policy,2001